The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00192-011-1607-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after native tissue vs. biological graft-augmented repair in the posterior compartment

Abstract: Long-term success of posterior repair is high. Graft augmentation does not appear to improve anatomic or functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In that study, the mesh was removed 30, 60, 90, 180, 360, 540, and 720 days after implantation and chronic inflammatory reactions around the mesh began to decrease 30 days after implantation, similar to what was observed in this study. Some studies have shown that while biological grafts are well tolerated and provide long-term success for pelvic floor reconstruction, this success rate is similar to that of traditional repair techniques that do not use graft materials [12,14,26] . However, this may be a result of material preparation.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, the mesh was removed 30, 60, 90, 180, 360, 540, and 720 days after implantation and chronic inflammatory reactions around the mesh began to decrease 30 days after implantation, similar to what was observed in this study. Some studies have shown that while biological grafts are well tolerated and provide long-term success for pelvic floor reconstruction, this success rate is similar to that of traditional repair techniques that do not use graft materials [12,14,26] . However, this may be a result of material preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Only other prospective cohort study by Goldstein et al reported 88% success rate based on mean Ba and Bp points at one year follow up. This group of 43 demonstrated no erosions and significant improvement in PDFI-20(pelvic floor distress inventory score) [8,22]. Xenform Soft tissue repair matrix is derived from fetal dermal bovine tissues [7][8][9][10][11][12] that, per World Health Organisation and European designation, has no known detectable prion infectivity.…”
Section: Discussionmentioning
confidence: 99%
“…The key in management of genital prolapse is to correct weak native fascial support. 12 The aim in genital prolapse management is to correct anatomical defects, restore sexual function, maintain urinary bladder and intestinal functions, prevent recurrence, and improve quality of life. 13 Sacrospinous ligament is attached from ischial spine to the lateral part of the sacrum, and its fixation keeps the vaginal axis in the midline.…”
Section: Jsafomsmentioning
confidence: 99%